Interspeech 2016 2016
DOI: 10.21437/interspeech.2016-1506
|View full text |Cite
|
Sign up to set email alerts
|

Between- and Within-Speaker Effects of Bilingualism on F0 Variation

Abstract: To what extent is prosody shaped by cultural and social factors? Existing research has shown that an individual bilingual speaker exhibits differences in framing, ideology, and personality when speaking their two languages. To understand whether these differences extend to prosody we study F0 variation in a corpus of interviews with German-Italian and German-French bilingual speakers. We find two primary effects. First, a betweenspeaker effect: these two groups of bilinguals make different use of F0 even when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…A person's language attributes, including accents and dialects, is one component within the individual system. Although we found evidence that the experience of linguistic profiling may vary based on who is judging the applicant (Seggie et al, 1986), which accents or dialects the applicant speaks with (Gomlich, 2020), and whether they are deemed as highly qualified based on their resume for the position (Voigt, 1994); the extant research overwhelmingly concludes that language, accents, and dialects influence interviewers' perceptions of a job candidate's employability across a variety of job types and organizational contexts. Eighty-three (83%) of the articles reported significant differences in listeners' ratings of perceived employability between speakers of differing accent and dialects.…”
Section: Individual System Componentsmentioning
confidence: 64%
See 1 more Smart Citation
“…A person's language attributes, including accents and dialects, is one component within the individual system. Although we found evidence that the experience of linguistic profiling may vary based on who is judging the applicant (Seggie et al, 1986), which accents or dialects the applicant speaks with (Gomlich, 2020), and whether they are deemed as highly qualified based on their resume for the position (Voigt, 1994); the extant research overwhelmingly concludes that language, accents, and dialects influence interviewers' perceptions of a job candidate's employability across a variety of job types and organizational contexts. Eighty-three (83%) of the articles reported significant differences in listeners' ratings of perceived employability between speakers of differing accent and dialects.…”
Section: Individual System Componentsmentioning
confidence: 64%
“…Other studies examined perceived employability under experimental conditions as rated by members of the general population (e.g., Hunt and Denim, 2022;Levon et al, 2021;Poels, 2021;Seggie et al, 1986); experienced employment interviewers and recruiters (e.g., Atkins, 1993;De La Zerda and Hopper, 1979;Hopper, 1977;Voigt, 1994); human resource management professionals (Blair and Conner, 1978;Carlson and McHenry, 2006;Terrell and Terrell, 1983;Rey, 1977); entrepreneurs (Seggie et al, 1986); and other professionals with managerial experience (e.g., Timming, 2017). In the studies where non-student listeners and raters were used, there were four experiments that concluded no differences in rating of employability based on vocal cues (Gomlich, 2020;Poels, 2021;Seggie et al, 1986;Voigt, 1994). These four studies represent 17% of the total number of studies (n 5 23) that engaged nonstudent listeners and raters.…”
Section: Organizational System Componentsmentioning
confidence: 99%
“…A intra-variabilidade pode ser referida como variabilidade intrínseca, ou variabilidade intrafalante. considerar seus efeitos juntamente com aqueles relacionados com a intervariabilidade [32] sempre que se for analisar o potencial discriminativo do referido parâmetro. Em estatística inferencial, o poder discriminativo de uma certa distribuição é referido como F-ratio [10] e é dado pela razão entre intervariabilidade/ e intravariabilidade.…”
Section: A Frequência Fundamental Como Parâmetro Fonético Forenseunclassified
“…There is a growing literature documenting the F0 profiles of different languages, and significant differences have been found for both typologically distinct (English and Japanese in Yamazawa & Hollien, 1992), and closely related languages (English and German in Mennen, Schaeffler, & Docherty, 2012). Bilinguals speaking their respective languages have also exhibited dissimilar F0 profiles (simultaneous bilinguals: Japanese-English in Graham, 2014; German-French and German-Italian in Voigt, Jurafsky, & Sumner, 2016), which in turn do not match those of monolingual native speakers (consecutive bilinguals compared to monolinguals: Japanese-English in Nariai & Tanaka, 2010). Such language-specific F0 patterns may result in variation in speaker age estimation across languages.…”
Section: Introductionmentioning
confidence: 99%
“…There could be several explanations for the null effect for the two European languages. First, the true difference in the two speaker groups’ production of variables implicated in speaker age estimation may approach zero due to substantial linguistic and sociocultural similarities (but note that Voigt et al, 2016 found significant differences in F0 profiles of the languages). It is also possible that geographical proximity allows for frequent contact, resulting in high cross-language familiarity and accuracy in assignment to social categories.…”
Section: Introductionmentioning
confidence: 99%